THE TEACHER AS ETHNOGRAPHER: NEGOTIATING IDENTITY WITH A STUDENT COMMUNITY IN NORTHERN CYPRUS - Turner, Dorothy (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2001)
ABSTRACT. This paper offers an illustration of a university teacher in the humanities representing her own classroom practice, lt recommends a dialogic model of the teacher as ethnographer, after the interlocutionary model proposed for anthropological study by the writings of James Clifford and others. The paper draws on material from three years' teaching experience in the Turkish Republic of Northern Cyprus, and recommends a model of classroom as 'society,' comprised of both students and teachers. It views the results of prolonged classroom interaction as a concrete 'utterance' in the Bakhtinian sense, and explores the textual representation of this dialogic relationship. LE PROFESSEUR-ETHNOGRAPHE: NÉGOCIATION DE L'IDENTITÉ DANS UNE COMMUNAUTÉ D'ÉTUDIANTS DANS LE NORD DE CHYPRE RÉSUMÉ. Cet article illustre la représentation qu'un professeur d'université en lettres se fait de sa propre pratique en classe. L'auteur recommande un modèle dialogique du professeur en tant qu'ethnographe, d'après le modèle interlocutionnaire que James Clifford et d'autres auteurs proposent pour les études anthropologiques. L'article s'appuie sur des données recueillies durant trois années d'enseignement dans le Nord de Chypre et propose un modèle en vertu duquel la salle de classe est une société constituée d'élèves et de professeurs. L'auteur considère les résultats d'une interaction en classe prolongée comme une énonciation concrète au sens bakhtinien du terme et examine la représentation textuelle de cette relation dialogique.